Peningkatan Kesejahteraan Psikologis Pengasuh Lansia Melalui Psikoedukasi Stres - Aulia, Astrina; Fitri, Miftahurrahmi; Deltu, Sri Nova; Putri, Anita Rahmawati; Aisy, Misbah Rihadatul (Abdimas Mandalika, 2025)
Abstract:  This community service program aimed to improve the psychological well-being of elderly caregivers through work stress psychoeducation and relaxation training at Aisyiyah Khusnul Khatimah Elderly Shelter in Padang. The methods included psychoeducation sessions with pre-test and post-test, leaflet distribution, relaxation practice (deep breathing, progressive muscle relaxation, mindfulness), and the establishment of a caregiver Standard Operating Procedure (SOP) that incorporates psychological well-being aspects. Evaluation was conducted using a knowledge questionnaire and the DASS-21 scale to assess depression, anxiety, and stress before and after the intervention. Results showed an increase in respondents’ knowledge about work stress from 62.5% (high category) to 87.5%. The DASS-21 results indicated significant improvement, with most respondents shifting to the normal category in depression (62.5%), anxiety (50%), and stress (75%) after relaxation practice. Overall, the program successfully enhanced caregivers’ soft skills in recognizing stress symptoms and coping strategies by approximately 70%. This community service was proven effective in strengthening caregivers’ capacity and is recommended to be replicated in similar caregiver communities.Abstrak: Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan kesejahteraan psikologis pengasuh lansia melalui psikoedukasi stres kerja dan pelatihan teknik relaksasi di Rumah Singgah Lansia Aisyiyah Khusnul Khatimah, Padang. Metode pelaksanaan meliputi penyuluhan dengan pre-test dan post-test, pembagian leaflet, praktik teknik relaksasi (napas dalam, relaksasi otot progresif, mindfulness), serta pengesahan Standar Operasional Prosedur (SOP) pelayanan pengasuh yang memuat aspek kesejahteraan psikologis. Evaluasi menggunakan kuesioner pengetahuan dan DASS-21 untuk mengukur depresi, kecemasan, dan stres sebelum serta sesudah intervensi. Hasil menunjukkan adanya peningkatan pengetahuan responden mengenai stres kerja dari kategori tinggi 62,5% menjadi 87,5%. Pengukuran DASS-21 memperlihatkan perbaikan signifikan, dengan mayoritas responden bergeser ke kategori normal pada subskala depresi (62,5%), kecemasan (50%), dan stres (75%) setelah pelatihan relaksasi. Secara keseluruhan, kegiatan ini berhasil meningkatkan soft skill pengasuh dalam mengidentifikasi gejala stres dan keterampilan teknik coping sebesar 70%. Program ini efektif dalam memperkuat kapasitas pengasuh lansia dan layak untuk direplikasi pada komunitas serupa